2012
DOI: 10.9753/icce.v33.structures.16
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism of Kamaishi Breakwaters Due to the Great East Japan Earthquake Tsunami

Abstract: Many breakwaters were damaged by the Great East Japan Earthquake of March 11, 2011. The majority of the breakwaters were destroyed or deformed under tsunami overflow; however, the failure mechanism under tsunami overflow is not clear. Therefore, with the main objective of this report being to clarify the stability of breakwaters under tsunami overflow, hydraulic model experiments and numerical simulations were conducted with Kamaishi Bay breakwaters as the subject, and failure mechanisms of the trunk of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…Bricker et al [2013a] showed that foundation-bearing capacity (punching) failure might also have contributed to the displacement of the caissons. However, the large-scale hydraulic laboratory experiments of Arikawa et al [2012] showed that sliding of the caissons atop their rubble mound was likely the major cause of failure. MLIT [2013a] agreed with this conclusion, and the Kamaishi breakwater is being rebuilt in nebaritsuyoi fashion, with a friction mat placed between caissons and the rubble mound, to reduce the likelihood of caisson sliding in the future [Japan Dredging and Reclamation Engineering Association, 2013].…”
Section: Breakwatersmentioning
confidence: 99%
“…Bricker et al [2013a] showed that foundation-bearing capacity (punching) failure might also have contributed to the displacement of the caissons. However, the large-scale hydraulic laboratory experiments of Arikawa et al [2012] showed that sliding of the caissons atop their rubble mound was likely the major cause of failure. MLIT [2013a] agreed with this conclusion, and the Kamaishi breakwater is being rebuilt in nebaritsuyoi fashion, with a friction mat placed between caissons and the rubble mound, to reduce the likelihood of caisson sliding in the future [Japan Dredging and Reclamation Engineering Association, 2013].…”
Section: Breakwatersmentioning
confidence: 99%
“…To wit, we are reminded of the Kamaishi breakwater, a pharaonic structure protecting Kamaishi, where no NPPs are located. Built at a cost of nearly US$1.5B, after more than three decades in construction, it was the largest and deepest breakwater in the world, and was located 215 km from Fukushima Dai-ichi (figure 1) and largely crumpled under the tsunami [27]. off-site AC power [12].…”
Section: Tsunami Settingmentioning
confidence: 99%
“…Widening work is considered one way to improve resilience. Arikawa et al (2013) clarified the effect of such widening work, allowing the measure to be implemented in many ports.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the damage was caused by tsunami overflows (Arikawa et al, 2012). Once protective facilities collapse, damage to the hinterland increases, so protective facilities should be designed to withstand tsunamis.…”
Section: Introductionmentioning
confidence: 99%